IMPLEMENTASI PERATURAN DAERAH NOMOR 3 TAHUN 2007 TENTANG PENGELOLAAN PASAR (STUDI KASUS DI PASAR RAYA SOLOK) - Wellizar Wellizar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Solok City Regional Regulation No. 3 of 2007 on the Market, aiming to provide guidance,regulation,structuring,control and supervision in order to empower small traders, medium, cooperatives and traditional markets to be resilient, advanced,independent and can improve well-being. The law is set before the enactment of Law No. 12 of 2011 on the Establishment oflegislation, and until now has not been implemented properly, because it does notinvolvethe publicin the preparation, andlack of socialization. The problems are: 1) How Implementation Regulation No. 3 of 2007? 2) What are the obstacles for Solok Government in implementing the Regulation on the Management of the Market? 3) What are the efforts made by the Government of Solok in Structuring Market? The method used in this research is a sociological juridical approach using secondary data and primary data through interviews, observation and document study. Market Research Location in Solok City.The Results of the study were 1) Implementing Regulation has not done well, the obstacles are a) The regulation has not been properly socialized, b) The Market Size is not proportional to the number of traders, limited human resources managers and traders Market c) The Worse drainage system. 3) Efforts have been made: a) Establishment of institutional, b) Management of Pasar Raya, c)Provision of support for market management.d) will revitalize the Pasar Raya Solok City which has been included in the 2021-2026 RPJM.